When police use force: context, methods, outcomes - Boylstein, Craig (Lynne Rienner Publishers, 2018)
Acknowledgments -- Defining police use of force -- The federal courts and police use of force -- Measuring police use of force -- Do police treat different groups differently? -- Current controversies in police use of force -- Demanding justice -- Policing as social control -- Appendix 1 Statistical tables -- Appendix 2 Statistical tables -- References